Neurotized Free Tissue Transfer for Foot Reconstruction: A Systematic Review - Rinkinen, Jacob R.; Diamond, Shawn; Lans, Jonathan; Cetrulo, Curtis L., Jr.; Eberlin, Kyle R. (Journal of Reconstructive Microsurgery, 2020)
Background Soft tissue reconstruction of the foot represents a complex reconstructive challenge given the unique anatomical properties of the glabrous plantar skin. For large soft tissue defects and/or complex injuries, free tissue transfer is often the optimal reconstructive modality. The decision to pursue a neurotized free flap remains controversial and an area of debate. Given the trend toward increasing use of neurotized free flaps, we performed a systematic review to determine if nerve coaptation is a beneficial adjunct to free tissue transfer.Methods A systematic search of the English literature using PubMed and Web of Science was performed. Studies were identified between 1985 and 2018. Manuscripts were eligible if they contained original clinical outcomes research of patients who underwent free tissue transfer to the foot or heel with neurotization.Results A total of 189 studies were identified with initial screening and 19 studies were included in our analysis. A total of 175 patients underwent free flap reconstruction to the foot; of these, 107 patients had a nerve coaptation performed. Patients who underwent neurotization had improved sensory characteristics (two-point discrimination, light touch, and pain sensation), quicker return to ambulation and activities of daily living, and decreased ulcer formation compared with those who did not. Overall complications were infrequent, with ulceration being the most common.Conclusion Neurotized free flaps appear to have an overall decreased rate of ulceration, improved sensory discrimination, and quicker return to ambulation/activities of daily living in comparison to nonneurotized free flaps. However, when examining free anterolateral thigh (ALT) and free medial plantar artery (MPA) fasciocutaneous flaps, durability (i.e., frequency of ulcer formation) and functionality (ambulation and return to activities of daily living) do not appear to be significantly different between neurotized and nonneurotized flaps.
Keywords: sensory flap; lower extremity reconstruction; neurotized flap